Preço de transferência no Brasil e os impactos nas demonstrações financeiras - Silva, Lourivaldo Lopes da (2008)
Until the end of 1.996, the Brazilian legislation did not regulate the transactions of importation and exportation related to companies from overseas. However, with the law number 9.430/96, January 1st, 1.997, the legislation for tax return regulated for the first time the issue about the cost for international transferring of goods, services, rights and interests. It was a big step to minimize the over costs on the importations and the under costs on the exportations. Several countries have been controlling all transferring of goods, services, rights and interests related to people from overseas for decades. In the United States of America they have adopted this process over 40 yeas ago. Several alterations have happened recently in the Brazilian Taxation scenario, especially with respect to cost transferring. This work is about the methodologies imposed by the Brazilian Legislation, for importation and exportation issues and to know if the current rules go against the Accounting Fundamental Principles and supplies recommendations to account the excess of costs from importing of goods, services and interests with companies from overseas